High Performance Networking, Computing, and Communication Systems Second International Conference, ICHCC 2011, Singapore, May 5-6, 2011. Selected Papers - Wu, Yanwen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed post-proceedings of the Second International Conference on Theoretical and Mathematical Foundations of Computer Science, ICTMF 2011, held in Singapore in May 2011. The conference was held together with the Second International Conference on High Performance Networking, Computing, and Communication systems, ICHCC 2011, which proceedings are published in CCIS 163. The 84 revised selected papers presented were carefully reviewed and selected for inclusion in the book. The topics covered range from computational science, engineering and technology to digital signal processing, and computational biology to game theory, and other related topics.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Computational complexity; Information storage and retrieval systems; Computer Science; Computer Communication Networks; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Discrete Mathematics in Computer Science; Computation by Abstract Devices; Data Structures, Cryptology and Information Theory